2023
DOI: 10.1037/met0000435
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating estimation problems in small sample structural equation modeling—A comparison of constrained maximum likelihood, Bayesian estimation, and fixed reliability approaches.

Abstract: Small sample structural equation modeling (SEM) may exhibit serious estimation problems, such as failure to converge, inadmissible solutions, and unstable parameter estimates. A vast literature has compared the performance of different solutions for small sample SEM in contrast to unconstrained maximum likelihood (ML) estimation. Less is known, however, on the gains and pitfalls of different solutions in contrast to each other. Focusing on three current solutions-constrained ML, Bayesian methods using Markov c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…The inequality constraint par > 0.01 was used where par was a loading or variance parameter. Previous research has shown that constrained (ML) estimation is preferable to unconstrained (ML) estimation in small samples because it solves convergence issues and substantially reduces variability in estimates [62,63].…”
Section: Methodsmentioning
confidence: 99%
“…The inequality constraint par > 0.01 was used where par was a loading or variance parameter. Previous research has shown that constrained (ML) estimation is preferable to unconstrained (ML) estimation in small samples because it solves convergence issues and substantially reduces variability in estimates [62,63].…”
Section: Methodsmentioning
confidence: 99%
“…Notably, many of the more advanced statistical approaches indeed require large samples, which may not be feasible given constraints on resources or the specific autistic sub‐population under study (e.g., childhood disintegrative disorder, autism associated with rare neurogenetic syndromes). In such cases, rather than attempt to utilize “large‐sample” statistical techniques, researchers are advised to use methods appropriate for the sample size, which may include classical test theory approaches (DeVellis, 2006; Nolte et al, 2019), Rasch models (Cleanthous et al, 2019; Petrillo et al, 2015), or Bayesian structural equation modeling (Smid et al, 2020; Ulitzsch et al, 2023) to analyze available data.…”
Section: Future Priorities For Proms In Autism Researchmentioning
confidence: 99%
“…However, we wanted to inform the readers about this issue, which is present in the structural equation model framework as a whole. When only very few observations are present in a mixture component, the component parameters should be interpreted with caution 20 . Models with less components or including more observations should also be considered.…”
Section: Identifiability and Interpretability Of The Modelmentioning
confidence: 99%